Chemical data of contaminants in water and sediments from the Doce River four years after the mining dam collapse disaster - Yamamoto, F. Y. [UNESP]; Pauly, G. E. [UNESP]; Nascimento, L. S.; Fernandes, G. M.; Santos, M. P.; Kim, B. S.M.; Carvalho, M. U. [UNESP]; Figueira, R. C.L.; Cavalcante, R. M.; Grassi, M. T.; Abessa, D. M.S. [UNESP] (Elsevier, 2022)
Chemical datasets describing the occurrence of both inorganic and organic contaminants along the Doce River Basin (DRB) could provide a better understanding of the potential impacts of a major mining dam collapse disaster combined to additional chronic sources of contamination. This data article presents datasets of main contaminants detected in the water and sediments sampled four years after the mining dam collapse in the DRB. A summary table of data obtained in the literature is also provided to allow a comparison of the variation of chemicals before, right after in 2015/2016 and after the event (current data). In addition, there are also provided physical-chemical parameters of water and sediments of different sampling sites, which could support the investigation of chemicals distribution. For this purpose, triplicate samples of water and sediment were obtained in 8 sampling sites along the DRB during wet and dry seasons of 2019, totalizing 48 samples of each environmental matrix. The sampling sites were strategically selected according to their different main sources of pollution along the river. Concentrations of trace elements and organic contaminants (polycyclic aromatic hydrocarbons, and pyrethroids) were determined in samples of water and sediments by inductively coupled plasma mass spectrometry (ICP-MS) and gas chromatography - mass spectrometry GC-MS, respectively. Main data obtained in the literature consisted in published reports from environmental agencies (IGAM) and private companies (RENOVA) as well as journal articles. The datasets provided may be useful to the stakeholders, which include scientific community, authorities and public agencies, and private companies interested to understand the impacts of the contaminants introduced along the River Basin four years after the environmental disaster.
Keywords: Brazil; Contamination; Iron tailing; Metals; PAHs